2011
DOI: 10.1186/1477-7819-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Emergency adrenalectomy due to acute heart failure secondary to complicated pheochromocytoma: a case report

Abstract: Pheochromocytomas are catecholamine producing tumors arising mostly from chromaffin cells of the adrenal medulla. The most common clinical presentation is hypertension, mainly in the form of paroxymal episodes. Cardiovascular manifestations include malignant arrhythmia and catecholamine cardiomyopathy, mimicking acute coronary syndromes and acute heart failure.There are reports of pheochromocytomas presenting as acute coronary syndrome and rapidly leading to cardiogenic shock; the failure of intensive medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…In a number of cases, IABP has been used to excellent effect . If IABP provides insufficient mechanical circulatory support, then extra‐corporeal life support (VA‐ECMO), through either femoral or central access, or cardiopulmonary bypass has been used successfully .…”
Section: Managementmentioning
confidence: 99%
“…In a number of cases, IABP has been used to excellent effect . If IABP provides insufficient mechanical circulatory support, then extra‐corporeal life support (VA‐ECMO), through either femoral or central access, or cardiopulmonary bypass has been used successfully .…”
Section: Managementmentioning
confidence: 99%
“…Previous case reports demonstrated that the cardiomyopathy can be reversed with surgical removal of pheochromocytoma 6 17. Our patient's ejection fraction increased from 10% on presentation to 55% prior to surgery after approximately 10 days of α and β blockade.…”
Section: Discussionmentioning
confidence: 50%
“…Paroxysmal symptoms usually last minutes to less than an hour; however, two documented episodes in our patient lasted greater than 4 h (see figure 1). Rarely, failure to diagnose and treat this condition can lead to congestive heart failure 5 6. The cause of the heart failure is unclear; however, catecholamine-induced cardiomyopathy or the abrupt withdrawal of catecholamine signalling in a patient with desensitised adrenoreceptors and a reduced circulatory volume may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…The treating physicians, however, elected to proceed with emergent adrenalectomy. The patient's haemodynamic and respiratory status greatly improved shortly after surgery [15].…”
Section: Initial Management: When Is It Appropriate To Operate?mentioning
confidence: 97%